Profitabilitas bank pembangunan daerah di indonesia periode tahun 2009-2013 - Charlie Oesin (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
This research aimed to analyze the influence of credit risk, liquidity, and operational efficiency on profitability of Regional Development Bank (BPD) in Indonesia period 2009-2013. The sample used in this study are 23 Regional Development Bank (BPD) using criteria through purposive sampling method. Analysis of the data used in this study is the classical assumption test and multiple linear regression.The results of this study indicate that the credit risk of significant negative influence on profitability, liquidity significant positive effect on profitability, and operational efficiency significant negative effect on profitability.Keywords : Credit Risk, Liquidity, Operational Efficiency, and Profitability.